Whole Exome Sequencing Identifies Multiple Diagnoses in Congenital Glaucoma with Systemic Anomalies - Reis, LM (2017)
The genetic basis of congenital glaucoma with systemic anomalies is largely unknown. Whole exome sequencing (WES) in 10 probands with congenital glaucoma and variable systemic anomalies identified pathogenic or likely pathogenic variants in three probands; in two of these, a combination of two Mendelian disorders was found to completely explain the patients' features whereas in the third case only the ocular findings could be explained by the genetic diagnosis. The molecular diagnosis for glaucoma included two cases with compound heterozygous or homozygous pathogenic alleles in CYP1B1 and one family with a dominant pathogenic variant in FOXC1; the second genetic diagnosis for the additional systemic features included compound heterozygous mutations in NPHS1 in one family and a heterozygous 18q23 deletion in another pedigree. These findings show the power of WES in the analysis of complex conditions and emphasize the importance of CYP1B1 screening in patients with congenital glaucoma regardless of the presence/absence of other systemic anomalies.